PENINGKATAN JIWA WIRAUSAHA SANTRI MELALUI PELATIHAN PEMANFAATAN SAMPAH PLASTIK MENJADI PRODUK BERNILAI JUAL - Etik Zukhronah; Winita Sulandari; Isnandar Slamet; Sri Subanti; Sugiyanto Sugiyanto; Irwan Susanto (Bajang Institute, 2023)
Lack of public understanding about the proper handling of plastic waste can damage the environment. Based on the results of a survey conducted on students at the Darul Muttaqin Islamic Boarding School, Sragen, it can be seen that the waste management in the boarding school has not been carried out properly. In general, waste is directly disposed of in a landfill, without prior sorting between organic and inorganic waste. In this case, the residents of the cottage have not tried to process waste, especially plastic waste into useful products. For this reason, the service team for the Statistics Study Program FMIPA UNS held a socialization and training on the use of plastic waste into ornamental flower products. The purpose of this activity is to equip students with skills, as well as to foster an entrepreneurial spirit by marketing products from plastic waste to the general public. In the end, the success of product marketing will provide its own advantages as an alternative source of income for the students. In the future, the activities carried out consistently and sustainably will not only provide good benefits for the students but also the preservation of the surrounding environment.